Randomized clinical trial of ultrasonic scissors versus conventional haemostasis to compare complications and economics after total thyroidectomy (FOThyr). Issue 1 (9th May 2017) - Blanchard, C.; Pattou, F.; Brunaud, L.; Hamy, A.; Dahan, M.; Mathonnet, M.; Volteau, C.; Caillard, C.; Durand‐Zaleski, I.; Mirallié, E.; ,
Abstract: Background: The benefits of single‐use ultrasonic scissors in thyroid surgery are still debated. Although this device has been shown to reduce operating time compared with conventional haemostasis, its cost‐effectiveness has never been demonstrated. The aim of this study was to evaluate the efficacy, cost‐effectiveness and safety of ultrasonic scissors for total thyroidectomy. Methods: This was a prospective, randomized, multicentre trial conducted at 13 hospital sites. The primary endpoint was the percentage of patients with hypocalcaemia (serum calcium level below 2 mmol/l) on day 2. Secondary endpoints included postoperative complications and costs, with calculation of incremental cost differences and cost‐effectiveness ratios. Results: In total, 1329 patients who underwent total thyroidectomy were included in the analysis: 670 were randomized to treatment with ultrasonic scissors and 659 to conventional haemostasis. There was no difference between groups in the rate of complications, including hypocalcaemia on day 2 (19 . 7 per cent in ultrasonic scissors group versus 20 . 3 per cent in conventional haemostasis group; P = 0·743). Median operating times were significantly shorter with ultrasonic scissors (90 versus 100 min with conventional haemostasis; P < 0·001). Total mean(s.d.) direct costs at 6 months were €4311(1547) and €4011(1596) respectively ( P < 0·001). Conclusion: Ultrasonic scissors were no more clinically effective than conventional haemostasis, but use of these devices was more costly. Registration number: NCT01551914 (http://www.clinicaltrials.gov ). Abstract : This randomized clinical trial compared ultrasonic scissors (US) and conventional haemostasis (CH) in total thyroidectomy. There was no between‐arm difference in the rate of postoperative (day 2) or definitive (6 months) complications (hypocalcaemia and recurrent nerve palsy). The shorter median operating time of 90 min (US) versus 100 min (CH) did not compensate for the higher cost of the US device. No real advantages